Prevalence, antimicrobial resistance and virulence genes characterization of nontyphoidal Salmonella isolated from retail chicken meat shops in Northern India. (August 2019) - Sharma, Jaishree; Kumar, Deepak; Hussain, Sheeba; Pathak, Anubha; Shukla, Maansi; Prasanna Kumar, V.; Anisha, P.N.; Rautela, Richa; Upadhyay, A.K.; Singh, S.P.
Abstract: The objective of this study was to determine the prevalence of antibiotic resistant nontyphoidal Salmonella in 39 retail chicken meat shops located in 7 towns of North India. Overall, nontyphoidal Salmonella prevalence of 9.43% (70/742) was observed. Highest Salmonella prevalence was observed in Lalkuan (20.99%). Chicken meat samples (40%) showed highest Salmonella prevalence followed by poultry feces (20%). Three serotypes of Salmonella were identified, Salmonella Kentucky ( S .Kentucky, 74.29%), Salmonella Virchow ( S .Virchow, 17.14%) and Salmonella Typhimurium ( S .Typhimurium, 7.14%). All isolates were multidrug resistant (MDR) by disk-diffusion assay, showing resistance to three or more classes of antibiotics. High resistance was observed to tetracycline (100%), erythromycin (100%), nalidixic acid (98.57%), ampicillin (95.71%) and ciprofloxacin (82.86%). Fifty-one (98.08%) S . Kentucky isolates were resistant to ciprofloxacin. Of these, 49 S . Kentucky isolates showed MIC values in the range of 3 to >256 μg/ml. Twenty-nine (41.43%) Salmonella isolates were co-resistant to ciprofloxacin and cefotaxime by disk-diffusion test. The tet A gene was detected in all Salmonella isolates and the bla TEM was the most predominant (25.37%) β-lactam gene. Multiple virulence genes such as sip A, mgt C, s op E1, s tn, sop B, fli C, spv C and gip A were also detected. High resistance to quinolone, cephalosporin and tetracycline antibiotics in nontyphoidal Salmonella isolates of poultry origin points towards their extra-label use in poultry farms. Highlights: Salmonella Kentucky as the predominant serotype in retail chicken shops. All Salmonella isolates (100%) are multidrug resistant. 41.43% Salmonella isolates co-resistant to ciprofloxacin and cefotaxime. High ciprofloxacin and levofloxacin MICs. bla TEM (25.37%) is the most predominant β-lactam gene detected.